Shariah-Compliant Digital Gold Saving - Muhammad Shahrim Sehak; Mohd Zulkifli Muhammad; Muhammad Zulfaris Mohd Salleh; Nurul Faizah Halim (Universiti Sains Islam Malaysia, 2025)
The Journal of Muamalat and Islamic Finance Research, Volume 22 Issue 1 Page (134–145)